An Approach to Construct a Metadata Graph for Specifying Enterprise Knowledge Graphs - Rolim, Tulio Vidal; Avila, Caio Viktor da Silva; Freitas, Renato; Mariano, Roberval Gomes; Vidal, Vania Maria Ponte (Anais do Simpósio Brasileiro de Banco de Dados (SBBD); 2024: Anais do XXXIX Simpósio Brasileiro de Bancos de Dados, 2024)
Enterprise Knowledge Graph (EKG) is a concept that is increasingly being used to process large volumes of data at the organizational level, however most efforts are concentrated on building the Data EKG, disregarding the metadata related to the entire data integration process. At this juncture, this work presents an approach for building a metadata graph for specifying EKGs. As a form of validation, a case study with part of the metadata graph is adopted.